2010
DOI: 10.1051/0004-6361/200913632
|View full text |Cite
|
Sign up to set email alerts
|

The earliest phases of high-mass star formation: the NGC 6334-NGC 6357 complex

Abstract: Context. Our knowledge of high-mass star formation has been mainly based on follow-up studies of bright sources found by IRAS, and has thus been incomplete for its earliest phases, which are inconspicuous at infrared wavelengths. With a new generation of powerful bolometer arrays, unbiased large-scale surveys of nearby high-mass star-forming complexes now search for the high-mass analog of low-mass cores and class 0 protostars. Aims. Following the pioneering study of Cygnus X, we investigate the star-forming r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
135
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 75 publications
(156 citation statements)
references
References 91 publications
18
135
3
Order By: Relevance
“…Integrating the estimated star formation rate in the Galactic disk (McKee & Williams 1997) within a volume of a 3 kpc radius suggests a star formation rate of ∼0.2 M /yr in the selected molecular cloud complexes. With such an estimate, and assuming a standard initial mass function (Kroupa 2001) and a lifetime of 1 × 10 5 yr (Motte et al 2007;Russeil et al 2010), the HOBYS survey should reveal about 250 high-mass protostars (from IR-quiet to IR-bright).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Integrating the estimated star formation rate in the Galactic disk (McKee & Williams 1997) within a volume of a 3 kpc radius suggests a star formation rate of ∼0.2 M /yr in the selected molecular cloud complexes. With such an estimate, and assuming a standard initial mass function (Kroupa 2001) and a lifetime of 1 × 10 5 yr (Motte et al 2007;Russeil et al 2010), the HOBYS survey should reveal about 250 high-mass protostars (from IR-quiet to IR-bright).…”
Section: Discussionmentioning
confidence: 99%
“…Given their high densities (∼10 5 cm −3 ) and cooler temperatures, they probably are gravitationally bound and represent the highmass analog of low-mass prestellar cores. These three objects are among the first massive prestellar cores, since virtually none have been detected in surveys of the Cygnus X and NGC 6334 complexes (Motte et al 2007;Russeil et al 2010).…”
Section: Discovery Of Intermediate-/high-mass Prestellar Coresmentioning
confidence: 99%
“…In Russeil et al (2010), we presented a census of highmass young stellar objects at various evolutionary stages: we identified 1 starless clump, 6 IR-quiet protostars, and 9 highluminosity IR protostars in NGC 6334-NGC 6357. Since the timescale of the high-mass young objects cannot be derived directly, a statistical method was used.…”
Section: The Ob Stars Censusmentioning
confidence: 99%
“…The extinction map and the morphology of the 1.2 mm cold dust emission seem to indicate that NGC 6334 and NGC 6357 are connected by a filamentary structure, suggesting that both regions belong to a single complex (Russeil et al 2010).…”
Section: Introductionmentioning
confidence: 98%
“…In contrast, a first attempt to obtain an unbiased sample using a complete dust continuum imaging at the scale of the molecular complex Cygnus X (Motte et al 2007) was able to derive some more systematic results on the existence of a cold phase (IR-quiet massive dense cores and Class 0-like massive protostars) for high-mass star formation (Bontemps et al 2010;Csengeri et al 2011). Another survey of the molecular complex NGC 6334/NGC 6357 was conducted by Russeil et al (2010), who identified IR-quiet massive dense cores and estimated highmass protostellar lifetimes. The IR-quiet massive dense cores are suggested to host massive class 0 protostars as seen by the Herschel Space Telescope (Nguyen Luong et al 2011a).…”
Section: Introductionmentioning
confidence: 99%